2018
DOI: 10.1103/physrevc.97.044322
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of α decay of nuclei around the Z=82, N=126 shell closures within the cluster-formation model and proximity potential 1977 formalism

Abstract: In the present work, we systematically study the α decay preformation factors Pα within the cluster-formation model and α decay half-lives by the proximity potential 1977 formalism for nuclei around Z = 82, N = 126 closed shells. The calculations show that the realistic Pα is linearly dependent on the product of valance protons (holes) and valance neutrons (holes) NpNn. It is consistent with our previous works [X.-D. Sun et al., Phys. Rev. C 94, 024338 (2016), J.-G. Deng et al., Phys. Rev. C 96, 024318 (2017)]… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 59 publications
1
35
0
1
Order By: Relevance
“…Recently, cluster formation model (CFM) [31,32,33,34,35] was proposed to extract the α-preformation factor in terms of the α-cluster formation energy based on the binding energy differences of the participating nuclide, which is in good agreement with different microscopical approaches. Deng et al [36] studied the α-decay halflives for nuclei around Z = 82, N = 126 closed shells by the proximity potential 1977 formalism; they confirmed that the effective and microscopic P α within the CFM reduce the discrepancy between theoretical and experimental data in the mentioned region.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, cluster formation model (CFM) [31,32,33,34,35] was proposed to extract the α-preformation factor in terms of the α-cluster formation energy based on the binding energy differences of the participating nuclide, which is in good agreement with different microscopical approaches. Deng et al [36] studied the α-decay halflives for nuclei around Z = 82, N = 126 closed shells by the proximity potential 1977 formalism; they confirmed that the effective and microscopic P α within the CFM reduce the discrepancy between theoretical and experimental data in the mentioned region.…”
Section: Introductionmentioning
confidence: 93%
“…where a α represents the superposition coefficient of the α-clusterization state Ψ α , E f α represents the formation energy of the α cluster, and E represents energy actually composed of the formation energy of the α cluster and the interaction energy between the α cluster and the daughter nuclei. Within the CFM, for eveneven nuclei, the α-clusterformation energy E f α and the total energy E of a considered system can be expressed as [55]…”
Section: The Total Wave Function Is An Eigenfunction Of the Totalmentioning
confidence: 99%
“…Alpha decay is an important decay mode that can give information about the structure of nuclei [1,2]. α−decay of nuclei have been investigated using various theoretical approaches such as the generalised liquid † email: wasiu.yahya@gmail.com, wasiu.yahaya@kwasu.edu.ng (1) 2 yahya˙Po˙DFM printed on November 11, 2021 drop model [3][4][5], the effective liquid drop model [6], the modified generalized liquid drop model [7][8][9], the fission-like model [10], the preformed cluster model [11,12], and cluster formation model [13][14][15][16]. These models use various interaction potentials ranging from the phenomenological potential such as the proximity potentials [17], the Woods-Saxon, squared Woods-Saxon, and Cosh potentials to microscopic interactions such as the double folding model.…”
Section: Introductionmentioning
confidence: 99%